A religião nos limites da simples educação: notas sobre livros didáticos e orientações curriculares de ensino religioso - Giumbelli, Emerson (Revista de Antropologia, 2010)
This article examines some official curriculum guidelines and textbooks of some major publishers directed to religious education - a discipline offered by public schools in Brazil. The goal is to know what in this material is defined as "religion" and how it organizes the universe resulting from that definition - especially the way it tackles what it would be common and what it would be specific to the particular religious traditions and groups. The inspiration for the analysis comes from authors who explore the disputed status of the category "religion". The article also discusses part of that literature and proposes avenues for future studies.